Implementasi Hukum Islam terhadap Jual Beli Garam Di Sumenep - Hali Makki (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2018)
Buying and selling is an activity that existed since immemorial time to the human, both Islamic and non-Islamic, buying and selling has a very binding law, and can be used as a foothold against the people who done agreemnet buying and selling. Something that we need to be considered and understand by sellers and buyers is to see the terms and pillar, as for the law that will be used as a reference that includes one aspect of them: Islamic law are a requirement and rukun buying and selling existing in the goods. The practice of buying and selling of salt at Alasmalang Village, Ra'as Sub-District of Sumenep Regency is valid because it is in accordance with the rules of sale and legal of Islam.